2016
DOI: 10.1155/2016/1971452
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress after Surgery on the Immature Heart

Abstract: Paediatric heart surgery is associated with increased inflammation and the production of reactive oxygen species. Use of the extracorporeal cardiopulmonary bypass during correction of congenital heart defects generates reactive oxygen species by various mechanisms: haemolysis, neutrophil activation, ischaemia reperfusion injury, reoxygenation injury, or depletion of the endogenous antioxidants. The immature myocardium is more vulnerable to reactive oxygen species because of developmental differences compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 96 publications
0
20
0
Order By: Relevance
“…Patients undergoing on-pump CABG surgery are affected by various ischemic stimuli: induction of cardioplegic arrest, microembolic events, reperfusion of the myocardium by surgical revascularization, and termination of cardioplegic arrest ( 18 ). There has been increasing evidence that the application of CPB using a heart-lung machine for open heart surgery may be the cause of some of this morbidity and is associated with pre- and postoperative stress responses, which triggers postoperative organ dysfunction ( 4 , 27 ). It is proposed that pretreatment with antioxidants such as Se could attenuate this inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients undergoing on-pump CABG surgery are affected by various ischemic stimuli: induction of cardioplegic arrest, microembolic events, reperfusion of the myocardium by surgical revascularization, and termination of cardioplegic arrest ( 18 ). There has been increasing evidence that the application of CPB using a heart-lung machine for open heart surgery may be the cause of some of this morbidity and is associated with pre- and postoperative stress responses, which triggers postoperative organ dysfunction ( 4 , 27 ). It is proposed that pretreatment with antioxidants such as Se could attenuate this inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In coronary artery bypass graft (CABG) surgery, reperfusion of the ischemic heart causes myocardial injury, which is exacerbated by cardioplegic arrest. During reperfusion injury, neutrophils are activated and an inflammatory response is triggered, leading to cytokine release and reactive oxygen species (ROS) generation ( 1 - 4 ). The imbalance between the ROS products and the ability of antioxidants to neutralize them results in oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to graft dysfunction, like allograft rejection, delayed graft function, or primary nonfunction, as well as to endothelial and parenchymal cell injury [52,53]. To increase success of the heart transplantation, experimental studies have focused on the enrichment of antioxidative substrates in cardioplegia solution and pump prime solution [54][55][56][57][58][59], suggesting the importance of continuous research into antioxidants.…”
Section: Int J Mol Sci 2020 21 X For Peer Review 3 Of 19mentioning
confidence: 99%
“…This study demonstrated a very large effect size, with NO being associated with a 50% relative reduction in the incidence of LCOS compared to children receiving standard treatment (15% compared to 31%, p = 0.007). The fact that this effect size was greatest in patients less than 2 years of age has biological plausibility; the neonatal/infant myocardium is more vulnerable to reactive oxygen species [12].…”
mentioning
confidence: 98%